Mechanism for Settlement of Wali Adhal Cases in the Determination of Guardian Judges in Banda Aceh - Cut Amirah Fatinah; Khairani Mukdin; Nik Salida Suhaila Nik Saleh; Rishat Ameer Ğafurof; Kasuwi Saiban (Yayasan Cendekia Gagayunan Indonesia, 2025)
This study aims to examine the factors that lead to the appointment of a marriage guardian judge (wali hakim) due to the refusal of a legitimate guardian (wali adhal), as well as the mechanism of its implementation at the Office of Religious Affairs (KUA) in Lueng Bata District, Banda Aceh. The research employs a qualitative approach with a sociological-empirical method, using in-depth interviews, observation, and documentation with the Head of KUA and KUA staff as the primary sources, supported by secondary data from literature and legal documents. The findings reveal that the appointment of a wali hakim generally arises from non-shar’i reasons, including personal conflicts between guardians and prospective brides, excessive social considerations related to the groom’s status, economic concerns, and long-standing family disputes. These factors restrict women’s rights to marry in accordance with Islamic law. The resolution mechanism consists of several stages, starting from reconciliation efforts, mediation by KUA and community leaders, and, if necessary, filing a petition to the Religious Court. Once the court transfers guardianship rights, the marriage can be solemnized with a wali hakim appointed by the judge. This study highlights the crucial role of KUA and the Religious Court in safeguarding women’s rights and ensuring the validity of marriage under both Islamic and state law in Indonesia.